Social Comparisons Under Pandemic Stress: Income Reference Groups, Comparison Patterns, and the Subjective Well-Being of German Students - Antje Jantsch; Gertrud Buchenrieder; Thomas Dufhues; Judith Möllers (Journal of Happiness Studies, 2024)
People use social comparisons to reduce uncertainty when facing new or stressful situations. This study explores how a stressful experience, the COVID-19 pandemic, changed how people compare their income. It relates these changes to subjective well-being (SWB). We use a repeated cross-sectional dataset of students at two German universities from before and during the pandemic. A novel survey instrument is employed to identify individualized reference groups used for income comparison and to analyze whether the comparison pattern changed. Our results reveal that, while there was little change in the size of the reference groups, there was some difference in the group composition. During the pandemic, survey respondents were more likely to select two types of individuals into their reference groups: relatives and people they only knew from social media. Income comparisons were beginning to have a negative association with SWB, while the relation had been positive before the pandemic. Moreover, upward income comparisons increased.
Keywords: 300; COVID-19; pandemic; reference group; comparison pattern; subjective well-being